Anatomy of Income and Wealth Inequality in the United States - Muczyk, Jan; Coccari, Ronald (Journal of Comparative International Management)

(untitled) (Management Futures, 2015)
Much has been written recently about the current income and wealth gaps in the U.S. and the causes proffered. They are: how U.S. elections are financed; offshoring of well-paid jobs; excessive executive salaries; decrease in private-sector unionization; inadequate education of the U.S. workforce; and the outsize return on capital. The authors assume that these are merely the visible manifestations of a larger underlying cause — "The Iron Law of Oligarchy." They identify the oligarchs, describe how they rule and the consequences, and propose ways to ameliorate the consequences.